Supporting Change in Literacy Instruction in Malawi - Sailors, Misty; Hoffman, James V.; Pearson, P. David; McClung, Nicola; Shin, Jaran; Phiri, Liveness Mwale; Saka, Tionge (Reading Research Quarterly, 2014)
In this study, we examined the effectiveness of an innovative approach to literacy instruction in Malawi on teachers' perceptions, attitudes, and instructional practices. Two groups participated in the study: Treatment teachers received complementary teaching and learning materials, workshops, and directive coaching, and control teachers received no intervention. After this five-month intervention, treatment teachers were significantly more comfortable with their languages of instruction and were more positive about their teaching ability, beliefs about the learning materials in their classroom, and beliefs about the culture of reading in their communities than control teachers were. There were no significant differences between groups when we analyzed their teaching practices or the engagement of their students. The coaching model proved to be associated with changes in teachers' beliefs and perceptions on many of our variables. These findings suggest that the program under examination was successful in promoting the conditions for success (teacher beliefs and perceptions). Further, the findings suggest that the implementation of coaching was an important source of support in implementing changes.
shortDOI: 10/ggvk3t KerkoCite.ItemAlsoKnownAs: 10.1002/rrq.70 10/ggvk3t 2339240:FPRQN6RV 2405685:IVTVDACJ
Keywords: Adult; C:Malawi; Childhood; Coaching; Decoding; Discussion; Early childhood; English as a second language; English for speakers of other languages; English language learners; English learners; Experimental; Fairy tales; Family literacy; Home language; Home-school connections; In-service; Instructional models; Language learners; Literature; Literature-based instruction; Oral language; Parental involvement; Phonics; Program evaluation; Reading strategies; Research methodology; School based; Sight words; Sociocultural; Socioeconomic factors; Strategies; Supplementary resources; Teacher education; Textbooks; and materials; folk tales; methods; phonemic awareness; phonological awareness; professional development; quasi-experimental; word recognition

Identifying strategies to enhance the educational inclusion of visually impaired children with albinism in Malawi - Lynch, Paul; Lund, Patricia; Massah, Bonface (International Journal of Educational Development, 2014)
Oculocutaneous albinism is an inherited condition with significant health and social impact on the lives of those affected throughout sub-Saharan, including in Malawi. Myths and superstitions surrounding the condition lead to stigmatisation, rejection and misconceptions. In a participatory study, consultations with educational professionals, children with albinism and their families documented the barriers to full educational access and revealed low-cost strategies that could be implemented in mainstream schools, to minimise the effect of the visual impairment associated with albinism. These were captured in two information booklets in English and vernacular, one for children and the other appropriate for teacher training.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2014.07.002 2339240:MXTDK768 2405685:K9AQNHDY
Keywords: Albinism; Resource centres; Special educational needs; Teacher training; Visual impairment

Education Sector Implementation Plan II (2013/14 - 2017/18) - Government of Malawi; UNICEF Malawi (2014)
KerkoCite.ItemAlsoKnownAs: 2339240:HJJGG7CU 2405685:2IVEYH7J

National ICT Master Plan - Government of Malawi (2014)
KerkoCite.ItemAlsoKnownAs: 2339240:JKYMAPAN 2405685:DGG93AXT

Mapping research and innovation in the Republic of Malawi - UNESCO Digital Library - Lemarchand, Guillermo A.; Schneegans, Susan (2014)
KerkoCite.ItemAlsoKnownAs: 2339240:2CHYB5HH 2405685:NLXSMGMX

Paying Per Diems for ICT4D Project Participation: A Sustainability Challenge - Sanner, Terje Aksel; Sæbø, Johan Ivar (Information Technologies & International Development, 2014)
The article highlights the contradictory role per diem payments play in swiftly attracting local participation in ICT for Development (ICT4D) projects, while undermining long-term capacity building and sustainability with such efforts. We discuss sustainability challenges endemic to ICT4D projects in light of our case study findings from a mobile phone–based intervention in a public health management information system (HMIS) in Malawi. We explore these challenges at multiple levels of analysis by drawing on the neo-institutional notion of “institutional logics.” For practitioners and policy makers, the article offers suggestions on how to counter some of the pitfalls associated with the use of per diems to incentivize ICT4D project participants. The study contributes to the institutional logics perspective by exploring empirically the intricate interdependence between two mutually reinforcing, yet seemingly incongruent institutional logics of development project impact and aid entitlement.
Number: 2 KerkoCite.ItemAlsoKnownAs: 2405685:E495PJBF
Keywords: ⛔ No DOI found